Wine tourism in Ukraine: status and prospects - Liubchenko, Valentyna; Kalenska, Vitalina (Eximia, 2025)
The article examines the current state and prospects for developing wine tourism in Ukraine in the context of growing interest in gastronomic travel. The features of the spatial location of wineries are determined, their tourist offers are analyzed, and the degree of digital presence is analyzed. Based on the collected empirical data, the author's structuring of the wine regions of Ukraine is carried out. The role of the winery brand as a factor in forming an authentic tourist experience is emphasized. Modern challenges, particularly the impact of martial law, are outlined, and proposals for further development of enogastronomic tourism in Ukraine are made.